2023
DOI: 10.1111/1747-0080.12834
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient content and cost of canned and dried legumes and plant‐based meat analogues available in New Zealand supermarkets

Leanne Young,
Sally Mackay,
Kathryn E. Bradbury

Abstract: AimsPlant‐based eating patterns are recommended for human and planetary health. Plant‐based protein sources in supermarkets include traditional options and plant‐based meat analogues. This cross‐sectional survey examined the nutritional content, healthiness, cost and labelling of these products.MethodsNutrient content and claims on canned legumes (plain [N = 64] and flavoured [N = 25]), canned baked beans (N = 23), dried legumes (N = 21), tofu (plain [N = 8] and flavoured [N = 5]), falafels (N = 14), meat anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Studies have consistently observed increased sales of promoted plant-based foods when promotions are in place, but no decreases in meat products which suggests increased purchases of promoted products rather than substitution for animal products, which may not achieve the intended shifts towards more sustainable diets [ 12 , 32 ]. Further, promotions in this study focused on plant-based alternatives, such as plant-based meats, which are perceived to be relatively expensive [ 33 ] and there have been concerns expressed that they are highly processed with potentially higher levels of sodium than the meat options [ 33 , 34 ]. Further research could consider how perceptions of promoted products may influence the impact of promotional activity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have consistently observed increased sales of promoted plant-based foods when promotions are in place, but no decreases in meat products which suggests increased purchases of promoted products rather than substitution for animal products, which may not achieve the intended shifts towards more sustainable diets [ 12 , 32 ]. Further, promotions in this study focused on plant-based alternatives, such as plant-based meats, which are perceived to be relatively expensive [ 33 ] and there have been concerns expressed that they are highly processed with potentially higher levels of sodium than the meat options [ 33 , 34 ]. Further research could consider how perceptions of promoted products may influence the impact of promotional activity.…”
Section: Discussionmentioning
confidence: 99%